IMPLEMENTASI PROGRAM KKN UNTUK PEMBERDAYAAN DAN PENGEMBANGAN DESA MELALUI PEMBIBITAN SAYUR, PENGELOLAAN SAMPAH, DAN PENDIDIKAN - Yoga Patriotisman Halawa; Suryani Buulolo; Ratapan Hulu; Agnes Andriani Wau; Aloysius Boby Halawa; Cindy Arlin Wau; Filipus Sukses Halawa; Insaf Peristiwa Ndruru; Srimuliati Dachi; Umarudin Halawa (Haga : Jurnal Pengabdian Kepada Masyarakat, 2025)
Village development through community empowerment is crucial to support the progress and well-being of villagers. The Community Service Program (KKN) in Soledua Village focused on three key issues: kale cultivation, waste management with bamboo bins, and improving the quality of education through private tutoring. These topics were chosen due to the village's limited yard agricultural productivity, low awareness of waste management, and limited access to additional education for children. The community service implementation method employed a participatory approach that actively involved villagers, through outreach, technical training, and direct mentoring during the KKN period. The results of the community service demonstrated a 30% increase in kale productivity, a 65% increase in waste management participation, and a 15% increase in student academic achievement. Furthermore, through the installation of house numbers and the construction of gates, the village supported orderly administration and a spirit of togetherness. In conclusion, the KKN program successfully increased the capacity of the Soledua Village community in local resource management and sustainable development, which can be used as a model for empowering other villages.